Challenges of Food Service towards Sustainability Beyond Food Waste - Rocha, Ada (2023)
Food service comprises the production of meals consumed outside the home, including consumers from all age groups and in different sectors, such as schools (from kindergarten to university), public and private companies, the health sector (from hospitals to elderly care institutions), military, sports facilities and restaurants (from fine dining to fast-food). Food service units (FSU) achieved importance and responsibility not only for feeding the population but also as an important setting for public health interventions, potentially educating consumers and modulating behaviours through the meals provided. In addition to its socioeconomic impact, the food service industry has a strong environmental impact. More sustainable food service starts with the basics: minimizing environmental impact by reducing carbon footprint. Food service industry is being encouraged to make choices that positively impact the environment. Nevertheless, most of the efforts and research made in the last years have been focused on evaluating and reducing food waste. This article focuses on strategies that could be implemented beyond food waste, and act on changing the food offer towards health and sustainability while promoting consumers behaviour change.